Expanding the Malaria Antibody Toolkit: Development and Characterisation of Plasmodium falciparum RH5, CyRPA, and CSP Recombinant Human Monoclonal Antibodies - Nacer, Adéla; Kivi, Gaily; Pert, Raini; Juronen, Erkki; Holenya, Pavlo; Aliprandini, Eduardo; Amino, Rogerio; Silvie, Olivier; Quinkert, Doris; Le Duff, Yann; Hurley, Matthew; Reimer, Ulf; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria, an infection caused by apicomplexan parasites of the genus Plasmodium, continues to exact a significant toll on public health with over 200 million cases world-wide, and annual deaths in excess of 600,000. Considerable progress has been made to reduce malaria burden in endemic countries in the last two decades. However, parasite and mosquito resistance to frontline chemotherapies and insecticides, respectively, highlights the continuing need for the development of safe and effective vaccines. Here we describe the development of recombinant human antibodies to three target proteins from Plasmodium falciparum: reticulocyte binding protein homologue 5 (PfRH5), cysteine-rich protective antigen (PfCyRPA), and circumsporozoite protein (PfCSP). All three proteins are key targets in the development of vaccines for blood-stage or pre-erythrocytic stage infections. We have developed potent anti-PfRH5, PfCyRPA and PfCSP monoclonal antibodies that will prove useful tools for the standardisation of assays in preclinical research and the assessment of these antigens in clinical trials. We have generated some very potent anti-PfRH5 and anti-PfCyRPA antibodies with some clones >200 times more potent than the polyclonal anti-AMA-1 antibodies used for the evaluation of blood stage antigens. While the monoclonal and polyclonal antibodies are not directly comparable, the data provide evidence that these new antibodies are very good at blocking invasion. These antibodies will therefore provide a valuable resource and have potential as biological standards to help harmonise pre-clinical malaria research.